THE EFFECT OF FEEDING Lactobacillus ON GROWTH, SURVIVAL RATE AND PROTEASE ACTIVITY OF Litopenaeus vannamei - Nunak Nafiqoh; Poh-Shing Chang; Yu-Chi Wang (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2011)
This study examined the effect of two Lactobacillus bacteria on protease activity and growth rate of Litopenaeus vannamei. An experiment was conducted to examine protease activity and growth rate. The experiment consisted of two treatment tanks, the first tank was provided with artemia immersed in 2.6 x 1016 cfu/mL of bacteria solution, the second tank served as the control tank. After 20 days, the L. vannamei in the tank that received Lactobacillus have significantly different in growth, survival rate and protease activity (P<0.05) compared to the control, but no significant difference between Lactobacillus casei and Lactobacillus plantarum treatments. Within the digestive organ, protease activity of hepatopancreas and stomach demonstrated significant higher activity (P<0.05) compared to the intestine.